2017
DOI: 10.1590/1982-0194201700030
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward privacy in social network and moral development of nursing students

Abstract: Objective: To compare attitudes toward privacy in with social network sites (SNSs) and moral development between undergraduates nursing and advertising students. Methods: Cross-sectional study conducted with 324 nursing students and 209 advertising students selected by convenience sampling method in two universities in South Korea. Data were collected by means of a questionnaire with Likert type responses, and analyzed descriptive and analytical statistics using SPSS. Results: The most posted subject and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Moreover, no significant difference in the attitude of nursing students toward social media in terms of sex was disclosed in this study. In the same way, a prior study found no significant difference in the attitude toward privacy in social networking sites between male and female students (Kim & An, 2017). However, one study revealed significant differences in sex regarding accountability related questions on social media (Cain et al, 2009).…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, no significant difference in the attitude of nursing students toward social media in terms of sex was disclosed in this study. In the same way, a prior study found no significant difference in the attitude toward privacy in social networking sites between male and female students (Kim & An, 2017). However, one study revealed significant differences in sex regarding accountability related questions on social media (Cain et al, 2009).…”
Section: Discussionmentioning
confidence: 57%